International case studies in the management of disasters : natural-manmade calamities and pandemics - George, Babu; Mahar, Qamar-ud-Din (Emerald Publishing Limited, 2020)
International Case Studies in the Management of Disasters presents a diverse range of case studies on how disasters, both natural and manmade, are being managed globally. This illuminating study draws on theories, models, and frameworks in the field of disaster management to explore a wide range of complex issues in specific disaster contexts. Showcasing internationally sourced case studies on disaster management, the collection comprehensively explores all aspects of the disaster management cycle. Authors are drawn from a diverse range of disciplinary and practical contexts, offering a wide variety of perspectives upon management of devastating events. A diverse compendium of issues is explored through case studies examining the management of hurricanes, droughts, floods, wildfires, terrorist activity and pandemics. Also examined in depth are governmental and non-governmental disaster management organizations, the role of the private sector in disaster management, and how innovative new technologies are being used in disaster situations.
Includes index.
Keywords: Emergency management -- Case studies.; Technology & Engineering, Emergency Management.; Crime & criminology.; elektronické knihy; electronic books